Inclusão escolar: um estudo das barreiras atitudinais - Zanzarini, Brena Santana (Universidade Federal de São Carlos, 2023)
Considering diversity, it is very important to study and reflect about inclusion, the pedagogical practices involved, and especially to relate it to natural sciences and social and emotional competences. And, through the political decisions made as a result of the historical processes it is noted that inclusion is one of the challenges most loaded with individual and collective psychological aspects. In this context, a major challenge is to associate inclusive education with the natural science disciplines, while it is necessary to understand what factors may be linked to the problems faced in the classroom with students targeted for special education and link the so-called social and emotional competencies. For this reason, this project aims to investigate the implications/interferences of attitudinal barriers in the teaching-learning process of students in the area of natural sciences and how this reflects on the inclusion process. The research was carried out in a school of the Pirassununga Board of Education, with semi-structured interviews for the respective teachers and resource room teachers who accompany the student. The methodology will adopt qualitative exploratory research assumptions, using Descriptive Textual Analysis techniques to analyze the text corpus, which will consist of transcribed interviews. As a result, it is expected that the research can contribute in several aspects research in the area of education, making data available for new work in teacher training and inclusive education; Contact of different education professionals, who may reflect on the way they deal with inclusive education, reflecting on the influence of attitudinal barriers in everyday school life; Structure possible didactic material for natural sciences teachers regarding inclusive education (first edition), with topics ranging from theoretical and practical content to assessments; Production of knowledge in the area, and articles to be published in scientific events and/or journals, to supply the lack of research in the area, as pointed out throughout the dissertation.
School inclusion: a study of attitudinal barriers
Keywords: Análise textual discursiva; Inclusão; Competências socioemocionais; Formação continuada; Discursive textual analysis; Inclusion; Socio-emotional skills; Continuing education; CIENCIAS HUMANAS::EDUCACAO